2018
DOI: 10.1007/s10620-018-5054-z
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine and Mobile Health Technology Are Effective in the Management of Digestive Diseases: A Systematic Review

Abstract: Telemedicine and mobile health technology may be effective in managing disease activity and improving quality of life in digestive diseases. Future studies should explore both gastrointestinal and gastroesophageal diseases using these types of interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 36 publications
2
47
0
1
Order By: Relevance
“…Medication and medical adherence have been found to improve following mHealth interventions in patients with digestive diseases such as IBD. 7,24 Adherence is especially important in digestive disease populations because these patients often have higher non-adherence rates compared to other chronic conditions, 7 and compliance with disease management protocols is an important predictor of positive long-term outcomes (i.e., reduced frequency of disease relapse). 24 It follows that increases in QoL scores often parallel successful disease management.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Medication and medical adherence have been found to improve following mHealth interventions in patients with digestive diseases such as IBD. 7,24 Adherence is especially important in digestive disease populations because these patients often have higher non-adherence rates compared to other chronic conditions, 7 and compliance with disease management protocols is an important predictor of positive long-term outcomes (i.e., reduced frequency of disease relapse). 24 It follows that increases in QoL scores often parallel successful disease management.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] mHealth technology can help patients adhere and comply with treatment, manage symptoms and medication, and monitor disease activity. 7 Findings from multiple studies have revealed that participants report more self-monitoring and better adherence to a weight management and/or dietary intervention when delivered via a smartphone app or personal digital assistant compared to a website or paper diary. [8][9][10][11] Wang et al 6 reported that patients who used smartphone apps felt secure knowing that their illness was closely monitored and were able to participate in their health management, and it gave them the feeling that they were well taken care of outside of the clinical setting and not forgotten by their doctors.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…High-speed telecommunications systems and the invention of devices capable of capturing and transmitting images in digital form had main roles in development [4] . Not only using proper hardware and software is essential, but we also need expert users [5]. There are four factors for prospering telemedicine: therapists' motivation, proper infrastructure, ongoing investment, and technical support [6].…”
Section: Introductionmentioning
confidence: 99%